2021
DOI: 10.1119/10.0005795
|View full text |Cite
|
Sign up to set email alerts
|

“Everyone is new to this”: Student reflections on different aspects of online learning

Abstract: In 2020, many instructors and students at colleges and universities were thrust into an unprecedented situation as a result of the COVID-19 pandemic disruptions. Even though they typically engage in in-person teaching and learning in brick and mortar classrooms, remote instruction was the only possibility. Many instructors at our institution who had to switch from in-person to remote instruction without any notice earlier in the year worked extremely hard to design and teach online courses to support their stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While course A occurred before the COVID-19 pandemic both courses B and C took place in Spring 2020 in the semester, resulting in an additional confounding factor that may have affected students' responses to our survey. Recent research into the effects of the sudden transition to online learning on students showed that online teaching negatively impacted student engagement and interaction between peers and with the instructors [40,41]. Students particularly missed opportunities to collaborate when doing lab activities online [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While course A occurred before the COVID-19 pandemic both courses B and C took place in Spring 2020 in the semester, resulting in an additional confounding factor that may have affected students' responses to our survey. Recent research into the effects of the sudden transition to online learning on students showed that online teaching negatively impacted student engagement and interaction between peers and with the instructors [40,41]. Students particularly missed opportunities to collaborate when doing lab activities online [41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research into the effects of the sudden transition to online learning on students showed that online teaching negatively impacted student engagement and interaction between peers and with the instructors [40,41]. Students particularly missed opportunities to collaborate when doing lab activities online [41]. Research suggests that students who are better at self-regulation/organization and who have better communication abilities are better equipped to succeed in the online learning environment [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Distance online teaching was carried out by various instructors, and students were also exposed to various teaching strategies. Different students' knowledge and perceptions of distance online teaching were analyzed by analyzing a large research school in the United States [16]. Al Mamun, M. A. et al pointed out that the increase in online learning triggered a focus on online teaching strategies, and the study focused on the impact of embedded instruction on students' online learning and explored online students' learning approaches [17].…”
Section: Introductionmentioning
confidence: 99%
“…To further highlight some major changes in the higher education paradigm during the pandemic, in lecture-based classes, students expressed the ability to re-watch lectures, attend classes on time and see and hear instructors better from the comfort of their home as part of advantages of online classrooms [25]. On the other hand, it was especially difficult for first year college students to make that transition from high school if their learning experiences were online, as that limited the level of interactions and collaborations they could avail.…”
Section: Common Teaching and Learning Strategies During The Pandemicmentioning
confidence: 99%